Delineation of mountains and mountain areas in Europe - a planning approach - Pantić Marijana (Zbornik Radova: Geografski institut "Jovan Cvijić", 2015)
Mountains are usually understood as high elevation areas, which are sparsely populated and where nature is preserved. The elevation above sea level is the most commonly taken as a criterion for mountain delineation, but the complexity of the task arises when definitions are compared in different national contexts, between projects and particularly when they are applied in decision-making process. Therefore, this paper aims to give a review of the existing palette of mountain definitions and mountain area delineations, to recognize some common criteria used in the definitions, as well as to review topics and situations in which the delineations are applied and used in spatial planning. Due to the diversity of cases, it was necessary to reduce scope of the topic; therefore the paper is limited to the European context and particularly to countries representing the largest European mountain massifs - Alps, Apennines, Pyrenees, Dinaric Alps and Carpathians.